2020
DOI: 10.5304/jafscd.2020.094.026
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Containment and Food Security in the Global South

Abstract: Population-level COVID-19 containment strategies have been particularly hard on the urban poor and vulnerable population groups such as female-headed households, children, youth, the homeless, informal sector employers and employees, casual workers, the unemployed, and migrants and refugees. As a direct result of the COVID-19 outbreak, a secondary pandemic of hunger and food insecurity is now impacting many of these groups. An effective and sustainable global response to the COVID-19 (and any further) viral pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 0 publications
1
36
2
Order By: Relevance
“…Additionally, food security issues emerged as a top priority besides health and safety concerns associated with the COVID-19 disease. The potential for a "secondary pandemic" of hunger and food shortage has become a serious concern for the Global South's urban poor and vulnerable groups (Crush and Si, 2020). Furthermore, countries or regions that rely heavily on food imports to meet domestic needs under normal conditions, such as the Pacific islands and territories (Farrell et al, 2020), have reported alarm regarding their food security vulnerability given COVID-19's global spread and the multitude of disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, food security issues emerged as a top priority besides health and safety concerns associated with the COVID-19 disease. The potential for a "secondary pandemic" of hunger and food shortage has become a serious concern for the Global South's urban poor and vulnerable groups (Crush and Si, 2020). Furthermore, countries or regions that rely heavily on food imports to meet domestic needs under normal conditions, such as the Pacific islands and territories (Farrell et al, 2020), have reported alarm regarding their food security vulnerability given COVID-19's global spread and the multitude of disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…This crisis is particularly pressing in low- and middle-income countries (LMICs), where food insecurity was already a serious concern prior to the COVID-19 pandemic [ 3 , 4 , 5 , 6 ]. Across LMICs, food security challenges are disproportionately felt by vulnerable populations, such as children, women, older adults, informal workers, and migrants and refugees, who may not have the financial or social capital to buffer against the shocks created by the pandemic [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say, it has been the urban poor who have suffered the most. Indeed, while food production, distribution, and retailing are generally considered 'essential services', many countries have allowed formal retailers, such as supermarkets and their supply chains, to remain operational, while shutting down the informal food sector on which the urban poor depend [10]. Furthermore, urban inhabitants do not have the natural endowments and easy access to areas of food production that rural areas enjoy.…”
Section: Introductionmentioning
confidence: 99%